2020
DOI: 10.1101/2020.09.29.20201509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laboratory evaluation of SARS-CoV-2 antibodies: detectable IgG up to 20 weeks post infection

Abstract: Background The SARS-CoV-2 pandemic necessitated rapid and global responses across all areas of healthcare, including an unprecedented interest in serological immunoassays to detect antibodies to the virus. The dynamics of the immune response to SARS-CoV-2 is still not well understood. Methods We measure SARS-CoV-2 antibody levels in plasma samples from 880 people in Northern Ireland by Roche Elecsys Anti-SARS-CoV-2 IgG/IgA/IgM, Abbott SARS-CoV-2 IgG and EuroImmun IgG SARS-CoV-2 ELISA immunoassays to analyse i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…The study findings contrast with those of an earlier study2—published as a preprint and not yet peer reviewed, which was funded by some of the consortium developing and producing the test—that suggested that the test gave no false positive results.…”
contrasting
confidence: 99%
“…The study findings contrast with those of an earlier study2—published as a preprint and not yet peer reviewed, which was funded by some of the consortium developing and producing the test—that suggested that the test gave no false positive results.…”
contrasting
confidence: 99%
“…The early IgG response is possibly a memory response from earlier coronavirus infection, producing cross-reactive antibodies that do not have neutralizing potency [52]. This was observed in several infections with closely related viruses, where some caused antibody-dependent enhancement (ADE) disease, leading to a worse clinical course [52,54]. In addition, this could explain why the symptomatic patients had a higher IgG detection rate than the asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to several reasons, including false-positive RT-PCR test, reactive RT-PCR with high CT value, an early-stage infection, a transient antibody response, no production of an antibody response, or production of antibodies that are below the detection level of the assays [36,37,39,48]. Some studies have indicated similar findings where they failed to detect a SARS-CoV-2 antibody response in variable portions of their COVID-19 sample cohorts [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…al. (2020) have very recently reported an antibody half-life of 85 days and a median time of 137 days to loss of positivity; these results are corrborated by Robertson et. al.…”
Section: Introductionmentioning
confidence: 59%